New Anchorage Technique for GFRP Flexural Strengthening of Concrete Beams Using Bolts-End Anchoring System - Djarir Yahiaoui; Mohamed Saadi (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The concept of external glass FRP composite confinement is a current process for strengthening concrete beams subjected to static loads. End anchorage glass FRP composites of 80 mm width and 90–130 mm length with different thicknesses (2.4 and 4.8 mm) have been fixed at the bottom of beams with bolts of various diameters (6 and 10 mm). It is concluded that the load capacity of the BEGFPC beams is improved by increasing the end-anchorage glass FRP composite thickness (about 98–188%). In addition, the BEGFPC system with bolts of 6 mm diameter has significantly improved the flexibility of beams. In contrast, the 10 mm bolts in diameter give a high ultimate load, whatever their quantity. Therefore, combining bolts with diameters of 6 and 10 mm would be the best solution for increasing the ultimate load and ductility of the retrofitted beams.